2015
DOI: 10.1080/09712119.2015.1013966
|View full text |Cite
|
Sign up to set email alerts
|

Effect of zilpaterol hydrochloride on animal performance and carcass characteristics in sheep: a meta-analysis

Abstract: The present study constitutes a meta-analysis of the use of zilpaterol hydrochloride (ZH) in sheep production (18 studies, n = 724 animals were evaluated), focused in its effects on productive performance and carcass characteristics in sheep who were given ZH in different doses (control 0, ≤0.50 and ≥0.54 mg/kg raised to the power 0.75 body weight (BW)). The analysis of the data assembled in the database was conducted by a statistical meta-analysis based on mixed model methodology. Results on weight gain were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 27 publications
3
4
0
3
Order By: Relevance
“…Zilpaterol is not currently labeled as a feed additive for lambs. The numerous studies conducted thus far in feedlot lambs adopted the labeled dosage as indicated for feedlot cattle [3,5,6,18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zilpaterol is not currently labeled as a feed additive for lambs. The numerous studies conducted thus far in feedlot lambs adopted the labeled dosage as indicated for feedlot cattle [3,5,6,18].…”
Section: Discussionmentioning
confidence: 99%
“…Increased HCW, LM area, and dressing percentage, and reduced backfat thickness with ZH supplementation has been a consistent response in feedlot lambs [18,21]. Increased LM area is partially explained by the greater ADG [22], whereas the increased dressing percentage is expected due to greater carcass protein accretion with no change in digestive tract fill [6,23].…”
Section: Discussionmentioning
confidence: 99%
“…However, lambs from those breeds have a lower growth rate, carcass yield, and meat quality compared with lambs from wool breeds [2]. The livestock and meat industry is constantly looking for alternatives to promote fast and efficient growth of livestock, and improve the carcass yield, i.e., increasing longissimus thoracis et lumborum (LTL) muscle area [3] or diminishing the fat content in the carcass [4]. Use of growth promoters, such as β-adrenergic agonists (β-AA), may improve growth and carcass characteristics of lambs from hair breeds.…”
Section: Introductionmentioning
confidence: 99%
“…Inesperadamente, los resultados de este estudio mostraron que el origen del sustrato energético usado para la formación de músculo en los corderos suplementados con CZ fue principalmente a partir de tejido adiposo y no de órganos, viseras, cabeza, patas o testículos. Este hallazgo coincide con otras investigaciones en ovinos donde usaron CZ de la empresa Zilmax® (6,18,28) , pero no con esas que suplementaron CZ de la empresa Grofactor® (22,23) como se hizo en este estudio. El CZ de Grofactor® (22,23) promueve en ovinos de engorda la formación de masa muscular por hacer uso de sustratos energéticos provenientes de una mejor repartición de energía dietaria, así como de algunos órganos, viseras o cabeza, pero no a partir de tejido graso.…”
Section: Discussionunclassified
“…El agonista adrenérgico β2 (AA β2) clorhidrato de zilpaterol (CZ) es un promotor de crecimiento que resulta efectivo para mejorar el comportamiento productivo y las características de la canal de importancia económica cuando se ofrece entre 4 y 5 semanas antes del sacrificio a corderos finalizados en corral (3)(4)(5)(6) , no así en pastoreo (7) . Este AA β2 funciona como promotor de crecimiento porque redistribuye sustrato energético del tejido graso y algunos órganos hacia la formación de masa muscular (hipertrofia) (4,8,9) .…”
Section: Introductionunclassified